How to Report: Ankle MRI - Antonio, Gregory E.; Griffith, James Francis (Seminars in Musculoskeletal Radiology, 2021)
Reporting ankle magnetic resonance imaging involves the assessment of multiple joints, tendons, and ligaments in several planes and numerous sequences. This article describes an approach using four anatomical categories (subcutaneous fat, bones and joints, tendons, and ligaments) to simplify and improve reporting efficiency. The main pathologies are covered, emphasizing the specific features to comment on, as well as suggesting terminology and phrases to use when reporting.
Keywords: magnetic resonance imaging; ankle; joint; tendon; ligament